Temporary Dwelling of Social Housing in Turin. New Responses to Housing Discomfort - Bau’, Giulia; Ingaramo, Luisa (TeMA - Journal of Land Use, Mobility and Environment, 2014)
In Turin the Compagnia di San Paolo had fostered two social housing initiatives, committed in handling the complex and fragmented housing discomfort issue. In the face of the social, economic and cultural development that has radically changed the housing emergency distinctive features, the new housing policies, realised with interventions of Edilizia Residenziale Sociale (ERS),  represent one possible response to the growing housing needs of a wide segment of population. The two temporary dwelling of social housing are born under a common denominator: the challenge has required the ability to find the balance between solidarity, social inclusion, housing rights and the real estate market. In the meantime they represent city laborato¬ries where testing good practices and innovative usual procedures and engine of new experiences and future experimentations.